Composição mineral e química em Panicum maximum cv. brs zuri submetida a diferentes níveis de salinidade e lâminas de irrigação - Silva, Eranildo Brasil da (2017)
The use of saline waters in irrigation of pastures may be a viable alternative, along with the use of salt tolerant cultivars. The objective of this work was to study the effects of different water depths and salinity levels on the growth of Panicum maximum cv. BRS Zuri. The experiment was conducted in a randomized complete block design with subdivided plots with five replicates per treatment. The treatments were the result of the combination of three salinity levels in the water (S1 = 0.6, S2 = 1.8, S3 = 3.0 dS m-1) and four irrigation intensities (I1 = 60, I2 = 80; I3 = 100, I4 = 120% of evapotranspiration). The chemical composition of the Panicum max cv. BRS Zuri, cut at 28 days, during two cycles, determining the dry matter (DM), crude protein (CP), mineral matter (MM), neutral detergent fiber (NDF), acid detergent fiber (FDA) extract ethereal (EE), hemicellulose (HEM), cellulose (CEL) and lignin (LIG). (N), phosphorus (P2O5), potassium (K2O), calcium (Ca), magnesium (Mg) and sodium (Na), expressed in g kg -1. There was interaction between the factors (salinity x lamina x cycle) for the dry matter contents, with the 2nd cycle superior to the 1st cycle in the 60% ET blade at salinity levels 1.8 and 3.0 dS m-1. With the increase of the irrigation slides, there was a linear reduction in crude protein contents in the two cycles. It was observed lower content of ethereal extract than 2nd cycle in relation to the 1st cycle in the salinity 1.8 dS m-1, in the slides 80 and 120% of ET. The neutral detergent fiber content increased linearly with irrigation slides in both cycles at salinity levels 0.6 and 1.8 dS m-1. There was no interaction (P> 0.05) between the factors (salinity x slide x cycle) for acid detergent fiber contents. However, there was a cycle x salinity interaction with a higher acid detergent fiber content than the first cycle at salinity of 0.6 dS m-1. In the first cycle, the highest hemicellulose content was observed in the salinity response of 3.0 dS m-1 in the 60% ET blade. Linear increases in cellulose contents were observed as a function of irrigation levels at salinity levels 1.8 and 3.0 dS m-1, not at the 2nd cycle. The lignin contents reduced linearly as irrigation slides, with decreases of 0.61 and 2.93 g kg-1 DM in lignin levels, respectively, in the 1st and 2nd cycle. It was observed interaction between the factors (salinity x blade x cycle) for the nitrogen contents. The first cycle was superior to the 2nd cycle only in the slides of 60 and 120% of ET in the salinities of 0.6 and 3.0 dS m-1, respectively. In the 1st cycle the phosphorus contents presented quadratic response in the salinity 0.6 dS m-1. In the second cycle, potassium levels were lower in slides 60, 100 and 120% of ET. No 1st cycle shows a higher calcium content in the 80% ET blade at salinities of 1.8 and 3.0 dS m-1. In the first cycle, it was observed that the magnesium contents reduced linearly with irrigation slides in the salinity of 0.6 dS m-1 and increased quadratically the salinity contents of 1.8 dS m-1 with the irrigation slides. It was observed a higher sodium content not 2nd cycle in relation to the 1st in the slide 60% of ET in the salinity 0.6 dS m-1. It was concluded that high levels of salinity (≥ 3.0 dS m-1) cause reductions in dry matter content as water availability and extension of the cultivar cycles increase. The reduction of saline levels of available low availability (60% of ET) to grosser crude protein. The salinity negatively affects the levels of neutral detergent fiber, acid detergent fiber, hemicellulose, cellulose and lignin, with the increase of the irrigation slides. There was a relationship between the minimum irrigation depth and the maximum values of the macrominerals studied, indicating that the effect of salinity becomes higher when the applied water is reduced, requiring a greater contribution of mineral contents by plants under these conditions.